Solid electrolyte, battery, method for producing solid electrolyte, and method for producing battery
By adopting a solid electrolyte of a specific composition and using the half-value width characteristics measured by X-ray diffraction, the reduction of the ion conductivity of the solid electrolyte in a high-temperature environment is suppressed, the problem of degradation of battery performance is solved, and better battery charging and discharging characteristics are achieved.
Patent Information
- Application Number
- CN202380058734.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-23
- Filing Date
- 2023-06-30
- Publication Date
- 2025-03-25
AI Technical Summary
The ion conductivity of solid electrolytes is easily reduced in high temperature environments, resulting in a decline in battery performance.
A solid electrolyte composed of LiαMβXγIδ, wherein M contains a metal element selected from Li and a semi-metal element, X includes F, Cl and Br. The Cu-Kα ray X-ray diffraction measurement shows that there is a peak with a half-value width of more than 0.10° and less than 0.55° in a specific diffraction angle range to suppress the decrease in ion conductivity.
It effectively suppresses the decrease in the ion conductivity of the solid electrolyte in a high temperature environment, and improves the output characteristics and charge and discharge performance of the battery.
Smart Images

Figure CN119698670A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a solid electrolyte, a battery, a method for producing a solid electrolyte, and a method for producing a battery. Background Art
[0002] Patent Document 1 discloses a halide containing iodine and usable as a solid electrolyte material.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2020 / 136952 Summary of the invention
[0006] Problem that the invention aims to solve
[0007] The ion conductivity of a solid electrolyte may decrease over time depending on the environment in which it is placed. An object of the present disclosure is to provide a solid electrolyte that suppresses the decrease in ion conductivity.
[0008] Solutions for solving problems
[0009] The present disclosure provides a solid electrolyte having a composition represented by the following formula (1):
[0010] Li α M β X γ I δ ……Formula (1)
[0011] In the above formula (1),
[0012] M includes at least one selected from the group consisting of metal elements and semi-metal elements other than Li,
[0013] X comprises at least one selected from the group consisting of F, Cl and Br,
[0014] satisfy:
[0015] 0<α、
[0016] 0<β、
[0017] 0≤γ, and
[0018] 0<δ,
[0019] In the X-ray diffraction pattern of the solid electrolyte obtained by X-ray diffraction measurement using Cu—Kα rays, there is a peak having a half-value width of 0.10° to 0.55° in the range of a diffraction angle 2θ of 31° to 32°.
[0020] Effects of the Invention
[0021] According to the present disclosure, a solid electrolyte in which a decrease in ion conductivity is suppressed can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a cross-sectional view showing a schematic structure of a solid electrolyte in Embodiment 1.
[0023] Figure 2 This is a flowchart showing an example of a method for producing a solid electrolyte in the first embodiment.
[0024] Figure 3 It is a cross-sectional view showing a schematic structure of a battery in Embodiment 2.
[0025] Figure 4 This is a flowchart showing an example of a method for manufacturing a battery in the second embodiment.
[0026] Figure 5 2 is a cross-sectional view showing a schematic structure of a solid electrolyte prepared in Example.
[0027] Figure 6 This is a graph showing a Cole-Cole plot obtained by impedance measurement of the solid electrolyte of Example 1.
[0028] Figure 7 Graphs showing X-ray diffraction patterns of the solid electrolytes of Example 1 and Comparative Example 1.
[0029] Fig. 8A It is a graph showing the X-ray diffraction patterns (30°≤2θ≤33°) of the solid electrolytes of Example 1 and Comparative Example 1 after the high-temperature retention test.
[0030] Figure 8B It is a graph showing the X-ray diffraction patterns (40°≤2θ≤44°) of the solid electrolytes of Example 1 and Comparative Example 1 after the high-temperature retention test. DETAILED DESCRIPTION
[0031] (Insights that form the basis of this disclosure)
[0032] It is known that a halide solid electrolyte containing iodine as a halogen has higher ion conductivity at 25° C. than a halide solid electrolyte not containing iodine.
[0033] On the other hand, the present inventors have conducted intensive research and found that the ion conductivity of a halide solid electrolyte containing iodine is greatly reduced when it is exposed to a high-temperature environment. As a result, the present inventors came up with the solid electrolyte disclosed herein.
[0034] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.
[0035] (Implementation Method 1)
[0036] Figure 1 2 is a cross-sectional view showing a schematic structure of solid electrolyte 10 in Embodiment 1. Solid electrolyte 10 in Embodiment 1 has a composition represented by the following formula (1).
[0037] Li α M β X γ I δ ……Formula (1)
[0038] In formula (1), M includes at least one selected from the group consisting of metal elements and semi-metal elements other than Li. X includes at least one selected from the group consisting of F, Cl and Br. Satisfies: 0<α, 0<β, 0≤γ, and 0<δ. The solid electrolyte 10 is a halide solid electrolyte containing iodine as a halogen.
[0039] In the present disclosure, "semi-metallic elements" include B, Si, Ge, As, Sb and Te. "Metallic elements" include all elements except hydrogen in Groups 1 to 12 of the periodic table, and all elements except B, Si, Ge, As, Sb, Te, C, N, P, O, S and Se in Groups 13 to 16. That is, "metallic elements and semi-metallic elements" are elements that can become cations when forming inorganic compounds with halogens.
[0040] The solid electrolyte 10 has higher ion conductivity than a halide solid electrolyte such as LiI formed of Li and halogen. Therefore, when the solid electrolyte 10 is used in a battery, the output characteristics of the battery can be improved.
[0041] In the X-ray diffraction pattern of the solid electrolyte 10 obtained by X-ray diffraction measurement, there is a peak having a half-value width FWHM of 0.10° or more and 0.55° or less in the range where the diffraction angle 2θ is 31° or more and 32° or less. The peak having a half-value width FWHM of 0.10° or more and 0.55° or less may be a peak having the highest intensity that exists in the range where the diffraction angle 2θ is 31° or more and 32° or less. In this specification, Cu-Kα rays are used for X-ray diffraction measurement.
[0042] When a halide solid electrolyte containing iodine is exposed to a high temperature environment, it decomposes to generate LiI. LiI contributes very little to ion conduction. Therefore, as the decomposition proceeds, the ion conductivity of the solid electrolyte becomes lower and lower. The decomposition of the solid electrolyte gradually develops from the surface of the solid electrolyte particles to the inside.
[0043] The half-value width FWHM of the X-ray diffraction peak is related to the crystallite size of the constituent material. The smaller the half-value width FWHM, the larger the crystallite size and the higher the crystallinity. The presence of a peak with a half-value width FWHM of 0.10° or more and 0.55° or less in the range where the diffraction angle 2θ is greater than 31° and less than 32° means that the crystallite size of the solid electrolyte 10 is relatively large. When the crystallite size is relatively large, there is a tendency that the size of the solid electrolyte particles is also large. If the size of the solid electrolyte particles increases, the specific surface area of the solid electrolyte particle group decreases. When the specific surface area of the solid electrolyte particle group is small, the solid electrolyte 10 is not easy to decompose and may also suppress the reduction of ion conductivity. In addition, when the crystallite size is relatively large, it is possible to suppress the phase transition from the crystal structure to the amorphous structure and / or the occurrence of strain in the crystal structure. That is, the crystal structure of the solid electrolyte 10 is stable. The crystal structure is stable and decomposition may also be suppressed.
[0044] The half-value width FWHM of the above-mentioned peak can be 0.10° or more and 0.40° or less, and more preferably 0.10° or more and 0.30° or less. That is, in the X-ray diffraction pattern of the solid electrolyte 10 obtained by X-ray diffraction measurement, there may be a peak with a half-value width FWHM of 0.20° or more and 0.40° or less in the range of the diffraction angle 2θ of 31° or more and 32° or less. According to such a configuration, a solid electrolyte 10 in which the reduction of ion conductivity is further suppressed can be provided.
[0045] In formula (1), M may include yttrium (Y). That is, the solid electrolyte 10 may include Y as a metal element. According to such a configuration, the ion conductivity of the solid electrolyte 10 can be improved.
[0046] In formula (1), M may include Y, and X may be Br γ1 Cl γ2 This means that 2.5≤α≤3.5, 0.5≤β≤1.5, 0≤γ1<6, 0≤γ2<6, 0<δ≤6, and γ1+γ2+δ=6 can be satisfied. With such a configuration, the ion conductivity of the solid electrolyte 10 can be further improved.
[0047] In formula (1), M may include Y, and X may be Br γ1 Cl γ2 This indicates that α=3, β=1, 0<γ1<6, 0<γ2<6, and 0<δ<6 can be satisfied. According to such a configuration, the ion conductivity of the solid electrolyte 10 can be further improved.
[0048] In formula (1), M may include Y, and X may be Br γ1 Clγ2 It indicates that α = 3, β = 1, γ1 = 2, γ2 = 2, and δ = 2 can be satisfied. That is, the solid electrolyte 10 can have a composition represented by Li3YBr2Cl2I2.
[0049] The solid electrolyte 10 may have, for example, Li 4.5 Y 0.6 Br2Cl2I2、Li 1.5 Y 1.5 Br2Cl2I2、Li3YBr 2.35 Cl2I 1.65 、Li3YBr2Cl3I、Li3YBr2Cl 3.5 I 0.5 、Li3YBrCl4I、Li3YBrCl 4.5 I 0.5 、Li3YBr 0.5 Cl5I 0.5 , Li3YCI4BrI, Li3YCI3Br2I, Li3YCI3BrI2, Li3YCI2Br3I, Li3YCI2BrI3, Li3YCIBr4I, Li3YCIBr3I2, Li3YCIBr2I3, Li3YCIBrI4, Li3YCI2Br 2.35 I 1.65 , Li 1.5 Y 1.5 CI2Br2I2、Li3YCI 3.5 B2I 0.5 、Li3YCI 4.5 B 0.5 、Li3YCI5Br 0.5 I 0.5 Composition shown.
[0050] Solid electrolyte 10 may contain inevitable impurities such as oxygen, water, and raw materials. The composition excluding the inevitable impurities can be represented by formula (1).
[0051] In the X-ray diffraction pattern of the solid electrolyte 10 after the high temperature retention test, the area intensity I d Relative to area intensity I m The ratio I d / I m It can be 0.01 or more and 0.70 or less. Here, the area intensity I m It is the peak area of the peak existing in the range of diffraction angle 2θ being 31° or more and 32° or less. Area intensity I dIt is the peak area of the peak existing in the range of diffraction angle 2θ being 42° or more and 43° or less. The high temperature holding test is a test of holding the solid electrolyte 10 for 100 hours in an environment of 100° or more and 150° or less. The temperature of "100° or more and 150° or less" is the ambient temperature.
[0052] The peak existing in the range of the diffraction angle 2θ being 31° or more and 32° or less is a peak derived from the solid electrolyte 10. The peak existing in the range of the diffraction angle 2θ being 42° or more and 43° or less is a peak derived from LiI generated by the decomposition of the solid electrolyte 10. Therefore, the ratio I d / I m It can be used as an indicator of the progress of decomposition of the solid electrolyte 10. d / I m A value of 0.01 or more and 0.70 or less indicates that decomposition of the solid electrolyte 10 is suppressed.
[0053] Ratio I d / I m It may be 0.30 or more and 0.60 or less. According to such a configuration, the solid electrolyte 10 in which the decrease in ion conductivity is suppressed is more reliably realized.
[0054] Area strength I m and area intensity I d It can be obtained by the following method. First, the data of the X-ray diffraction pattern is fitted using a Gaussian function or a Lorentzian function. During the fitting, the noise is eliminated by smoothing the data. Based on the fitted data, the area intensity I is obtained. m and area intensity I d .
[0055] The solid electrolyte 10 may be a molded body. The solid electrolyte 10 may be formed into a molded body together with other materials constituting the battery, such as an active material.
[0056] <Method for producing solid electrolyte>
[0057] A method for producing the solid electrolyte 10 will be described. Figure 2 1 is a flowchart showing an example of a method for producing the solid electrolyte 10 .
[0058] First, a solid electrolyte material is prepared (step S1). The obtained solid electrolyte material is in powder form. As a method for preparing a solid electrolyte material, a sintering method, a mechanochemical grinding method, etc. can be listed. In this specification, "solid electrolyte material" refers to a material before heat treatment (step S3) after synthesis.
[0059] In the calcination method, the mixed material is calcined at a temperature of 200° C. to 650° C. The calcination can be performed in a vacuum or in an inert gas atmosphere. Examples of the inert gas include nitrogen and rare gases.
[0060] In the mechanochemical milling method, mixed materials are reacted with each other in a mixing device such as a planetary ball mill.
[0061] According to these methods, a solid electrolyte material having a composition represented by the following formula (1) can be obtained.
[0062] Li α M β X γ I δ ……Formula (1)
[0063] In formula (1), M includes at least one selected from the group consisting of metal elements and semi-metal elements other than Li, X includes at least one selected from the group consisting of F, Cl and Br, and the following conditions are satisfied: 0<α, 0<β, 0≤γ and 0<δ.
[0064] The mixed material used in step S1 is obtained by mixing raw material powders prepared to a target composition. The raw material powders are, for example, LiBr, LiI, YBr3 and YCl3. As an example, when the target composition is Li3YBr2Cl2I2, the mixture is mixed at a molar ratio of LiBr:LiI:YBr3:YCl3=1:2:0.33:0.67. In order to offset the composition changes that may occur during the synthesis process, the raw material powders may also be mixed at a pre-adjusted molar ratio.
[0065] In the calcination method, when the calcination temperature is 200°C or higher, the mixed material can be reacted sufficiently. In addition, by setting the calcination temperature to 650°C or lower, the thermal decomposition of the halide produced by the solid phase reaction can be suppressed. As a result, the ion conductivity of the obtained solid electrolyte material can be improved.
[0066] In the calcination method, for example, a powdery mixed material is placed in a container and calcined in a heating furnace. Examples of the container include a crucible. The calcination time is, for example, 15 minutes to 12 hours.
[0067] In the calcination method, the mixed material can be calcined at a temperature of 200°C or more and less than 500°C. When the calcination temperature is less than 500°C, the thermal decomposition of the halide can be further suppressed. By calcining at a temperature less than 500°C, i.e., the melting point of LiI contained in the mixed material, the decomposition of LiI before the solid phase reaction is completed can be suppressed. Thus, a solid electrolyte material having a composition represented by formula (1) can be synthesized more reliably.
[0068] In the calcination method, the mixed material may be calcined at a temperature of 380° C. or higher and lower than 500° C. When the calcination temperature is 380° C. or higher, the crystallinity of the solid electrolyte material can be improved. When the crystallinity is improved, the ion conductivity of the solid electrolyte material is improved.
[0069] Next, the solid electrolyte material is molded to obtain a molded body (step S2 ).
[0070] In step S2, a molded body can be produced by press-molding the solid electrolyte material. The shape of the molded body is not particularly limited, for example, a plate-like shape. The temperature of the press-molding is, for example, above room temperature (25° C.) and below 500° C. The pressure of the press-molding is, for example, 10 MPa to 720 MPa. The time of the press-molding is, for example, 5 seconds to 1 hour. Step S2 is preferably implemented in a vacuum or in an inert gas atmosphere.
[0071] In addition, when the press molding in step S2 is performed at a temperature of 200° C. or higher and lower than 500° C., step S3 described later may be omitted.
[0072] The filling rate of the molded body obtained in step S2 is, for example, 80% or more. The upper limit of the filling rate of the molded body obtained in step S2 is not particularly limited. The upper limit is, for example, 99.5%. The filling rate of the molded body can be calculated by the following formula (2).
[0073] Filling rate (%) = 100 - porosity (%) ... Formula (2)
[0074] The porosity can be obtained, for example, by the following method. First, a cross section of the molded body is exposed and observed using a scanning electron microscope (SEM). In the cross-sectional SEM image, the porosity can be obtained by dividing the total area of the pore portion of the molded body by the total area of the molded body including the pores.
[0075] Finally, the molded body is fired at a temperature of 200° C. or higher and lower than 500° C. (step S3). In this way, solid electrolyte 10 can be obtained. Step S3 can be performed in a vacuum or in an inert gas atmosphere.
[0076] The firing time in step S3 is, for example, 15 minutes to 12 hours.
[0077] The calcination temperature in step S3 is more preferably 250° C. or higher and lower than 350° C. (ambient temperature). According to such a configuration, it is possible to produce a solid electrolyte 10 in which a decrease in ion conductivity is further suppressed.
[0078] As described above, the solid electrolyte 10 can be obtained by heat treating a molded body of a solid electrolyte material having a composition shown in formula (1). It should be noted that the composition of the solid electrolyte material does not change before and after the above-mentioned heat treatment. In the solid electrolyte 10 manufactured by the above-mentioned method, the reduction in ion conductivity is suppressed. It is speculated that the reason is that the crystal structure of the solid electrolyte material changed by the press molding in step S2 is close to the original state due to the firing of step S3. In other words, it is speculated that the reason is that the crystallite size of the solid electrolyte material increases due to the firing of step S3.
[0079] (Implementation Method 2)
[0080] Hereinafter, the battery 100 in Embodiment 2 will be described. The description overlapping with that in Embodiment 1 will be omitted as appropriate.
[0081] Figure 3 1 is a cross-sectional view showing a schematic structure of a battery 100 in Embodiment 2. The battery 100 includes a positive electrode 12, a negative electrode 13, and a solid electrolyte layer 11 disposed between the positive electrode 12 and the negative electrode 13. At least one selected from the group consisting of the positive electrode 12, the negative electrode 13, and the solid electrolyte layer 11 includes the solid electrolyte 10 in Embodiment 1. In the solid electrolyte 10, a decrease in ion conductivity is suppressed, so that the battery 100 can have excellent charge and discharge characteristics.
[0082] According to the above-described mechanism, even if the solid electrolyte 10 is included in any of the positive electrode 12 , the negative electrode 13 , and the solid electrolyte layer 11 , a desired effect can be obtained.
[0083] The solid electrolyte 10 may be included in only one selected from the group consisting of the positive electrode 12 , the negative electrode 13 , and the solid electrolyte layer 11 , may be included in two of them, or may be included in all three of them.
[0084] In the present embodiment, the solid electrolyte layer 11 is in contact with the positive electrode 12 and the negative electrode 13 .
[0085] The solid electrolyte 10 may be contained in the solid electrolyte layer 11. If the solid electrolyte 10 is contained in the solid electrolyte layer 11, the charge and discharge characteristics of the battery 100 are further improved.
[0086] The solid electrolyte layer 11 may contain 100% by mass of the solid electrolyte 10 with respect to the whole solid electrolyte layer 11, excluding impurities inevitably mixed therein. That is, the solid electrolyte layer 11 may be substantially composed of only the solid electrolyte 10. The solid electrolyte layer 11 may also be the solid electrolyte 10 itself.
[0087] The solid electrolyte layer 11 contains the solid electrolyte 10 as a main component, and may further contain inevitable impurities, or initial raw materials, by-products, and decomposition products used when synthesizing the solid electrolyte 10. The ratio of the mass of the solid electrolyte 10 to the mass of the solid electrolyte layer 11 may be, for example, 50% by mass or more, or 70% by mass or more.
[0088] The positive electrode 12, for example, contains a material having the property of absorbing and releasing metal ions (for example, lithium ions) as a positive electrode active material. As the positive electrode active material, for example, lithium-containing transition metal oxides, lithium-containing transition metal phosphates, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal oxysulfides, transition metal oxynitrides, etc. can be used. As lithium-containing transition metal oxides, Li(Ni, Co, Al)O2, Li(Ni, Co, Mn)O2, LiCoO2, etc. can be listed. In particular, when using lithium-containing transition metal oxides as positive electrode active materials, it is possible to reduce manufacturing costs and increase the average discharge voltage of the battery 100.
[0089] In the present disclosure, "(Ni, Co, Al)" means at least one element selected from the element group in parentheses. That is, "(Ni, Co, Al)" has the same meaning as "at least one selected from the group consisting of Ni, Co and Al". The same applies to other elements.
[0090] The positive electrode 12 may include an electrolyte material, for example, a solid electrolyte. The solid electrolyte included in the positive electrode 12 may also include a halide solid electrolyte.
[0091] The halide solid electrolyte may be a compound that does not contain sulfur. In the case of not containing sulfur, generation of hydrogen sulfide can be prevented.
[0092] The positive electrode 12 may include the solid electrolyte 10 in Embodiment 1 as a halide solid electrolyte. According to the above configuration, the output characteristics of the battery 100 can be further improved.
[0093] The positive electrode 12 may use a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, a complex hydride solid electrolyte, or the like, in addition to the halide solid electrolyte.
[0094] As sulfide solid electrolytes, Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 etc. LiX, Li2O, MO can also be added to theseq , Li p MO q Here, X is at least one selected from the group consisting of F, Cl, Br and I. M is at least one selected from the group consisting of P, Si, Ge, B, Al, Ga, In, Fe and Zn. p and q are natural numbers. A sulfide solid electrolyte selected from one or more of the above materials can be used.
[0095] As oxide solid electrolytes, there are NASICON-type solid electrolytes represented by LiTi2(PO4)3 and its elemental substitution products, (LaLi)TiO3-based perovskite-type solid electrolytes, and Li 14 ZnGe4O 16 , LISICON solid electrolytes represented by Li4SiO4, LiGeO4 and their elemental substitutes, Li7La3Zr2O 12 Garnet-type solid electrolytes represented by element substitutions thereof, glass or glass ceramics in which Li2SO4, Li2CO3, etc. are added to Li-BO compounds such as Li3PO4 and its N substitutions, LiBO2, Li3BO3, etc. An oxide solid electrolyte selected from one or more of the above materials can be used.
[0096] As a polymer solid electrolyte, for example, a compound of a polymer compound and a lithium salt can be used. The polymer compound can have an ethylene oxide structure. The polymer compound having an ethylene oxide structure can contain a large amount of lithium salt. Therefore, the ion conductivity can be further improved. As lithium salts, LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, etc. can be listed. One lithium salt can be used alone, or two or more can be used in combination.
[0097] Examples of complex hydride solid electrolytes include LiBH4-LiI, LiBH4-P2S5, and the like.
[0098] The negative electrode 13, for example, contains a material having the property of absorbing and releasing metal ions (for example, lithium ions) as a negative electrode active material. The negative electrode active material can use metal materials, carbon materials, oxides, nitrides, tin compounds and silicon compounds. The metal material can be a single metal. The metal material can also be an alloy. Examples of metal materials include lithium metal and lithium alloys. Examples of carbon materials include natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite and amorphous carbon. The capacity density can be improved by using silicon (Si), tin (Sn), silicon compounds and tin compounds. Examples of oxides include Li4Ti5O 12 , LiTi2O4, TiO2, etc.
[0099] The negative electrode 13 may include an electrolyte material, for example, a solid electrolyte. The solid electrolyte included in the negative electrode 13 may also include a halide solid electrolyte.
[0100] The negative electrode 13 may include the solid electrolyte 10 in Embodiment 1 as a halide solid electrolyte. According to the above configuration, the output characteristics of the battery 100 can be further improved.
[0101] As the solid electrolyte contained in the negative electrode 13, in addition to the halide solid electrolyte, for example, a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte can be used. According to the above configuration, the output characteristics of the battery 100 can be further improved. As the sulfide solid electrolyte, the oxide solid electrolyte, the polymer solid electrolyte, and the complex hydride solid electrolyte, the materials exemplified as the solid electrolyte contained in the positive electrode 12 can be used.
[0102] <Battery Manufacturing Method>
[0103] A method for manufacturing the battery 100 will be described. Figure 4 1 is a flowchart showing an example of a method for manufacturing the battery 100 .
[0104] First, a solid electrolyte material is prepared (step ST1). The obtained solid electrolyte material is in a powdery state. Step ST1 is the same as step S1 in the method for producing the solid electrolyte 10, and therefore its description is omitted.
[0105] Next, a stacked body including the positive electrode 12, the solid electrolyte layer 11, and the negative electrode 13 is produced (ST2). Examples of the method for producing the stacked body include a wet method and a dry method.
[0106] In the wet method, for example, a laminate can be made using the following method. First, a positive electrode slurry containing a solid electrolyte material and a positive electrode active material, and a negative electrode slurry containing a solid electrolyte material and a negative electrode active material are prepared separately. The positive electrode slurry is applied to the positive electrode collector and dried. The negative electrode slurry is applied to the collector and dried. As needed, the coating film can also be pressurized. In this way, a positive electrode 12 and a negative electrode 13 can be obtained. The solid electrolyte layer 11 can be obtained by applying a slurry containing a solid electrolyte material to a substrate and drying it. The solid electrolyte layer 11 can also be obtained by forming a thin film of a solid electrolyte material on a substrate by sputtering or evaporation and drying it. Next, the solid electrolyte layer 11 is arranged between the positive electrode 12 and the negative electrode 13 and is pressurized and integrated. In this way, a laminate is formed.
[0107] The solid electrolyte layer 11 can be formed by applying a slurry containing a solid electrolyte material to the surface of the positive electrode 12. The negative electrode 13 can also be integrated by placing it on the solid electrolyte layer 11 formed on the surface of the positive electrode 12 and press-molding, thereby forming a laminate. The solid electrolyte layer 11 can be formed by applying a slurry containing a solid electrolyte material to the surface of the negative electrode 13. The positive electrode 12 can also be integrated by placing it on the solid electrolyte layer 11 formed on the surface of the negative electrode 13 and press-molding, thereby forming a laminate. The solid electrolyte layer 11 can be formed by applying a slurry containing a solid electrolyte material to the surfaces of the positive electrode 12 and the negative electrode 13, respectively. The solid electrolyte layer 11 formed on the surface of the positive electrode 12 can also be integrated by bringing the solid electrolyte layer 11 formed on the surface of the negative electrode 13 into contact and press-molding, thereby forming a laminate.
[0108] In the case of a wet method, step ST1 includes a heat treatment for drying each coating film. The temperature of the heat treatment is appropriately set according to the solvent used. After the heat treatment, a laminate including the positive electrode 12, the solid electrolyte layer 11, and the negative electrode 13 is produced.
[0109] In the dry method, for example, a laminate can be made by the following method. First, the lower mold is inserted into an insulating tube, and then a solid electrolyte material is added. The upper mold is inserted into the insulating tube, and the solid electrolyte material is pressurized to form a solid electrolyte layer 11. The upper mold is removed, and a positive electrode material containing a solid electrolyte material and a positive electrode active material is added to the insulating tube. The upper mold is inserted into the insulating tube again, and the positive electrode material is pressurized to form a positive electrode 12 on the solid electrolyte layer 11. After the positive electrode 12 is formed, the lower mold is removed, and a negative electrode material containing a solid electrolyte material and a negative electrode active material is added to the insulating tube. The lower mold is inserted again, and the negative electrode material is pressurized to form a negative electrode 13. Thus, a laminate is formed.
[0110] The filling rate of the laminate obtained in step ST2 is, for example, 80% or more. The upper limit of the filling rate of the laminate obtained in step ST2 is not particularly limited. The upper limit is, for example, 99.5%. The filling rate of the laminate can be obtained by the same method as the filling rate of the molded body.
[0111] It should be noted that generally, sulfide solid electrolytes and polymer solid electrolytes have lower heat resistance than halide solid electrolytes. Therefore, considering the sintering temperature in step ST3 performed after step ST2, the positive electrode 12, the solid electrolyte layer 11 and the negative electrode 13 preferably do not contain sulfide solid electrolytes and polymer solid electrolytes.
[0112] Finally, the stacked body is fired at a temperature of 200° C. to less than 500° C. (step ST3). Thus, the battery 100 can be obtained. Step ST3 is the same as step S3 in the method for producing the solid electrolyte 10, except that the stacked body is fired instead of the formed body, so the description thereof is omitted.
[0113] In the above example, positive electrode 12, solid electrolyte layer 11 and negative electrode 13 all contain solid electrolyte 10. However, at least one selected from the group consisting of positive electrode 12, solid electrolyte layer 11 and negative electrode 13 may contain solid electrolyte 10.
[0114] As solid electrolyte layer 11 , solid electrolyte 10 itself in Embodiment 1 may be used. For example, when solid electrolyte layer 11 only includes solid electrolyte 10 , solid electrolyte 10 itself can be used as solid electrolyte layer 11 , and therefore step ST3 may be omitted.
[0115] (Other embodiments)
[0116] (appendix)
[0117] Based on the description of the above embodiments, the following technology is disclosed.
[0118] (Technology 1)
[0119] A solid electrolyte having a composition represented by the following formula (1):
[0120] Li α M β X γ I δ ……Formula (1)
[0121] In the above formula (1),
[0122] M includes at least one selected from the group consisting of metal elements and semi-metal elements other than Li,
[0123] X comprises at least one selected from the group consisting of F, Cl and Br,
[0124] satisfy:
[0125] 0<α、
[0126] 0<β、
[0127] 0≤γ, and
[0128] 0<δ,
[0129] In the X-ray diffraction pattern of the solid electrolyte obtained by X-ray diffraction measurement using Cu—Kα rays, there is a peak having a half-value width of 0.10° to 0.55° in the range of a diffraction angle 2θ of 31° to 32°.
[0130] In the solid electrolyte of Technology 1, a decrease in ion conductivity is suppressed.
[0131] (Technique 2)
[0132] The solid electrolyte according to the technique 1, wherein in the above formula (1), M includes Y. According to such a configuration, the ion conductivity of the solid electrolyte can be improved.
[0133] (Technique 3)
[0134] The solid electrolyte according to technology 1 or 2, wherein in the above formula (1), X is Br γ1 Cl γ2 This means that the following conditions are satisfied: 2.5≤α≤3.5, 0.5≤β≤1.5, 0≤γ1<6, 0≤γ2<6, 0<δ≤6, and γ1+γ2+δ=6. According to such a configuration, the ion conductivity of the solid electrolyte can be further improved.
[0135] (Technique 4)
[0136] A battery comprising:
[0137] positive electrode,
[0138] Negative electrode, and
[0139] a solid electrolyte layer disposed between the positive electrode and the negative electrode,
[0140] At least one selected from the group consisting of the positive electrode, the negative electrode, and the solid electrolyte layer includes the solid electrolyte according to any one of Techniques 1 to 3.
[0141] In the battery of Technology 4, the decrease in ion conductivity of the solid electrolyte is suppressed, so that excellent charge and discharge characteristics can be achieved.
[0142] (Technique 5)
[0143] A method for manufacturing a solid electrolyte, comprising the following operations:
[0144] shaping the solid electrolyte material to obtain a shaped body; and
[0145] The molded body is fired at a temperature of 200° C. or higher and lower than 500° C.,
[0146] The solid electrolyte material has a composition represented by the following formula (1):
[0147] Li α M β X γ I δ ……Formula (1)
[0148] In the above formula (1),
[0149] M includes at least one selected from the group consisting of metal elements and semi-metal elements other than Li,
[0150] X comprises at least one selected from the group consisting of F, Cl and Br,
[0151] satisfy:
[0152] 0<α、
[0153] 0<β、
[0154] 0≤γ, and
[0155] 0<δ.
[0156] According to the manufacturing method of the technique 5, a solid electrolyte in which a decrease in ion conductivity is suppressed can be manufactured.
[0157] (Technique 6)
[0158] The method for producing a solid electrolyte according to technique 5, wherein in the above formula (1), X is Br γ1 Cl γ2 This means that the following conditions are satisfied: 2.5≤α≤3.5, 0.5≤β≤1.5, 0≤γ1<6, 0≤γ2<6, 0<δ≤6, and γ1+γ2+δ=6. According to such a configuration, the ion conductivity of the solid electrolyte can be further improved.
[0159] (Technique 7)
[0160] The method for producing a solid electrolyte according to the technique 5 or 6, wherein the filling rate of the molded body is 80% or more. With such a configuration, the ion conductivity of the solid electrolyte can be improved.
[0161] (Technology 8)
[0162] The method for producing a solid electrolyte according to any one of techniques 5 to 7 includes the following steps: preparing the solid electrolyte material by mixing raw material powders and firing them. With such a configuration, the ion conductivity of the solid electrolyte can be improved.
[0163] (Technique 9)
[0164] A method for manufacturing a battery, comprising the following operations:
[0165] preparing a stacked body in which a positive electrode, a solid electrolyte layer, and a negative electrode are sequentially arranged; and
[0166] The laminate is fired at a temperature of 200° C. or higher and lower than 500° C.,
[0167] At least one selected from the group consisting of the positive electrode, the negative electrode, and the solid electrolyte layer contains a solid electrolyte material,
[0168] The solid electrolyte material has a composition represented by the following formula (1):
[0169] Li α M β X γ I δ ……Formula (1)
[0170] In the above formula (1),
[0171] M includes at least one selected from the group consisting of metal elements and semi-metal elements other than Li,
[0172] X comprises at least one selected from the group consisting of F, Cl and Br,
[0173] satisfy:
[0174] 0<α、
[0175] 0<β、
[0176] 0≤γ, and
[0177] 0<δ.
[0178] According to the manufacturing method of technology 9, the decrease in the ion conductivity of the solid electrolyte is suppressed, so it is possible to manufacture a battery having excellent charge and discharge characteristics.
[0179] (Technology 10)
[0180] The method for manufacturing a battery according to technology 9, wherein in the above formula (1), X is Br γ1 Cl γ2This means that the following conditions are satisfied: 2.5≤α≤3.5, 0.5≤β≤1.5, 0≤γ1<6, 0≤γ2<6, 0<δ≤6, and γ1+γ2+δ=6. According to such a configuration, the ion conductivity of the solid electrolyte can be further improved.
[0181] (Technology 11)
[0182] The method for manufacturing a battery according to the technique 9 or 10, wherein the filling rate of the stacked body is 80% or more. With such a configuration, the ion conductivity of the solid electrolyte can be improved.
[0183] (Technology 12)
[0184] The method for manufacturing a battery according to any one of techniques 9 to 11 further includes the following operation: preparing the solid electrolyte material contained in the positive electrode, the solid electrolyte layer, and the negative electrode by mixing and sintering the raw material powders. According to such a configuration, the ion conductivity of the solid electrolyte can be improved.
[0185] Example
[0186] Hereinafter, the details of the present disclosure will be described using Examples and Comparative Examples.
[0187] [Production of solid electrolyte materials]
[0188] In a glove box with an argon atmosphere at a dew point below -60°C, weigh LiBr, LiI, YBr3 and YCl3 as raw material powders in a molar ratio of LiBr:LiI:YBr3:YCl3=1:2:0.33:0.67. These raw material powders are crushed and mixed in an agate mortar to obtain a mixed material. Next, the obtained mixed material is placed in an alumina crucible, heated to 440°C, and sintered for 1 hour. The obtained sintered product is crushed using an agate mortar. Thus, a powder of a solid electrolyte material represented by the composition formula of Li3YBr2Cl2I2 is obtained.
[0189] [Preparation of solid electrolyte]
[0190] 《Example 1》
[0191] 150 mg of the powder of the solid electrolyte material prepared by the above method was press-molded at room temperature and a pressure of 720 MPa for 5 minutes to prepare a molded body of Example 1. The filling rate calculated by the above method was 99%.
[0192] Next, the obtained molded body was placed on a hot plate made of SUS, the temperature of the hot plate was raised to 300° C., and calcined for 1 hour. Thus, the solid electrolyte of Example 1 was obtained. The solid electrolyte of Example 1 was in the shape of a disk having a diameter of 9.2 mm and a thickness of about 600 μm.
[0193] Comparative Example 1
[0194] A press-molded solid electrolyte of Comparative Example 1 was prepared in the same manner as the solid electrolyte of Example 1 except that the calcination after press-molding was omitted. The solid electrolyte of Comparative Example 1 was in a disk shape with a diameter of 9.2 mm and a thickness of about 600 μm.
[0195] (Evaluation of ion conductivity)
[0196] Figure 5 1 is a cross-sectional view showing a schematic structure of a solid electrolyte 50 produced in the embodiment. First, the two main surfaces 501 and 502 of the solid electrolyte 50 are respectively brought into contact with SUS needles. Next, an impedance analyzer is connected to the front end of each needle, and the solid electrolyte 50 is kept at room temperature. In this state, the ionic conductivity of the solid electrolyte 50 is measured. The ionic conductivity is measured using a complex impedance method.
[0197] Figure 6 This is a graph showing a Cole-Cole plot obtained by impedance measurement of the solid electrolyte of Example 1. Figure 6 In FIG. 1 , the vertical axis represents the imaginary part of impedance, and the horizontal axis represents the real part of impedance.
[0198] Figure 6 In the equation, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the solid electrolyte to ion conduction. Figure 6 The arrow R SE Using this resistance value, the ion conductivity was calculated based on the following formula (3).
[0199] σ=(R SE ×S / t) -1 ……Formula (3)
[0200] In the formula (3), σ represents the ion conductivity. S represents the area of the main surface of the solid electrolyte. SE represents the resistance value of the solid electrolyte in the impedance measurement. t represents the thickness of the solid electrolyte.
[0201] Based on the formula (3), the ion conductivity of the solid electrolytes in Example 1 and Comparative Example 1 was calculated. The results are shown in Table 1 below.
[0202] (X-ray diffraction measurement)
[0203] X-ray diffraction measurement was performed on the solid electrolytes of Example 1 and Comparative Example 1. For the X-ray diffraction measurement, a powder X-ray diffractometer (MiniFlex600 manufactured by Rigaku Corporation) was used. The measurement conditions were as follows.
[0204] X-ray source: Cu-Kα ray (wavelength: 0.15406nm)
[0205] Measuring range: 2θ = 10° to 80°
[0206] Sampling step width: 0.01°
[0207] Scanning speed: 10° / min
[0208] Figure 7 Graph showing X-ray diffraction patterns of the solid electrolytes of Example 1 and Comparative Example 1 obtained by X-ray diffraction measurement. Figure 7 The half-value width FWHM of the peak of the solid electrolyte which is the peak having the highest intensity within the range of the diffraction angle 2θ of 31° to 32° in Example 1 and Comparative Example 1 was calculated. The results are shown in Table 1 below.
[0209] (High temperature retention test)
[0210] Next, a high-temperature retention test was performed on each of the solid electrolytes of Example 1 and Comparative Example 1 under the following conditions.
[0211] First, the solid electrolyte was kept for 100 hours in an environment of 125° C. After 100 hours, the solid electrolyte was naturally cooled until it reached 25° C.
[0212] The ion conductivity of the solid electrolytes of Example 1 and Comparative Example 1 after the high temperature retention test was calculated by the above method. The ion conductivity maintenance rate after the high temperature retention test was calculated based on the ion conductivity before and after the high temperature retention test. The results are shown in Table 1 below.
[0213] Furthermore, X-ray diffraction measurement was performed on the solid electrolytes of Example 1 and Comparative Example 1 after the high-temperature retention test by the above-mentioned method. Fig. 8A and Figure 8B It is a graph showing the X-ray diffraction patterns of the solid electrolytes of Example 1 and Comparative Example 1 after the high-temperature retention test. Fig. 8A The 2θ range is shown to be 30° to 33°. Figure 8B The 2θ range is 40° to 44°. Fig. 8A and Figure 8B , calculate the ratio I of the solid electrolyte of Example 1 and Comparative Example 1d / I m The peak present in the range of the diffraction angle 2θ being 31° or more and 32° or less is the peak of the solid electrolyte. That is, the area intensity I m The peak area of the peak of the solid electrolyte. The peak existing in the range of the diffraction angle 2θ being 42° or more and 43° or less is the peak of LiI generated by the decomposition of the solid electrolyte. That is, the area intensity I d is the peak area of the peak of LiI. It should be noted that the data fitting, smoothing and calculation of each area intensity were performed using software attached to a powder X-ray diffraction apparatus (MiniFlex600 manufactured by Rigaku Corporation). The results are shown in Table 1 below.
[0214] [Table 1]
[0215]
[0216] Investigation
[0217] The ion conductivity maintenance rate of the solid electrolyte of Example 1 is much higher than that of the solid electrolyte of Comparative Example 1. That is, in Example 1, the decrease in ion conductivity caused by the high temperature retention test is suppressed. d / I m It is suppressed lower than that in Comparative Example 1. It is understood that when the half value width FWHM of the peak existing in the range of the diffraction angle 2θ of 31° to 32° is 0.10° to 0.55°, the decrease in ion conductivity is suppressed.
[0218] In Example 1, the molded body of the solid electrolyte material having the composition represented by composition formula (1) was fired at a temperature of 200° C. to less than 500° C. It is presumed that the crystallite size in the solid electrolyte increased, the crystal structure was stabilized, and the progress of decomposition was suppressed.
[0219] In the above-mentioned embodiment, the solid electrolyte represented by Li3YBr2Cl2I2 is used to evaluate the ion conductivity. However, it is speculated that even if at least one of the group consisting of metal elements and semi-metal elements other than Li is used instead of Y, such as lanthanide elements (for example, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb or Lu), the same degree of effect can be obtained. This is because lanthanide elements have the same electronic configuration as yttrium, and the atomic radius is also similar, so they can have a similar structure.
[0220] Industrial Applicability
[0221] The solid electrolyte disclosed herein can be used in, for example, lithium-ion secondary batteries for vehicles.
Claims
1. A solid electrolyte having a composition represented by the following formula (1), Li α M β X γ I δ …… Formula (1) In the formula (1), M includes at least one selected from the group consisting of metal elements and semi-metal elements other than Li, X comprises at least one selected from the group consisting of F, Cl and Br, satisfy: 0<α、 0<β、 0≤γ, and 0<δ, In the X-ray diffraction pattern of the solid electrolyte obtained by X-ray diffraction measurement, there is a peak having a half-value width of 0.10° to 0.55° in the range of a diffraction angle 2θ of 31° to 32°.
2. The solid electrolyte according to claim 1, wherein In the formula (1), M contains Y.
3. The solid electrolyte according to claim 1, wherein In the formula (1), X by Br γ1 Cl γ2 express, satisfy: 2.5≤α≤3.5、 0.5≤β≤1.5、 0≤γ1<6, 0≤γ2<6, 0<δ≤6, and γ1+γ2+δ=6.
4. A battery comprising: positive electrode, Negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode, At least one selected from the group consisting of the positive electrode, the negative electrode, and the solid electrolyte layer includes the solid electrolyte according to any one of claims 1 to 3.
5. A method for manufacturing a solid electrolyte, comprising the following operations: molding the solid electrolyte material to obtain a molded body; and The molded body is fired at a temperature of 200° C. or higher and lower than 500° C., The solid electrolyte material has a composition represented by the following formula (1): Li α M β X γ I δ …… Formula (1) In the formula (1), M includes at least one selected from the group consisting of metal elements and semi-metal elements other than Li, X comprises at least one selected from the group consisting of F, Cl and Br, satisfy: 0<α、 0<β、 0≤γ, and 0<δ.
6. The method for producing a solid electrolyte according to claim 5, wherein: In the formula (1), X by Br γ1 Cl γ2 express, satisfy: 2.5≤α≤3.5、 0.5≤β≤1.5、 0≤γ1<6, 0≤γ2<6, 0<δ≤6, and γ1+γ2+δ=6.
7. The method for producing a solid electrolyte according to claim 5, wherein: The filling rate of the molded body is 80% or more.
8. The method for manufacturing a solid electrolyte according to claim 5, further comprising the following operations: The solid electrolyte material is prepared by mixing raw material powders and firing them.
9. A method for manufacturing a battery, comprising the following operations: preparing a stacked body in which a positive electrode, a solid electrolyte layer, and a negative electrode are sequentially arranged; and The laminate is fired at a temperature of 200° C. or higher and lower than 500° C., At least one selected from the group consisting of the positive electrode, the negative electrode, and the solid electrolyte layer contains a solid electrolyte material, The solid electrolyte material has a composition represented by the following formula (1): Li α M β X γ I δ …… Formula (1) In the formula (1), M includes at least one selected from the group consisting of metal elements and semi-metal elements other than Li, X comprises at least one selected from the group consisting of F, Cl and Br, satisfy: 0<α、 0<β、 0≤γ, and 0<δ.
10. The method for manufacturing a battery according to claim 9, wherein: In the formula (1), X by Br γ1 Cl γ2 express, satisfy: 2.5≤α≤3.5、 0.5≤β≤1.5、 0≤γ1<6, 0≤γ2<6, 0<δ≤6, and γ1+γ2+δ=6.
11. The method for manufacturing a battery according to claim 9, wherein: The filling rate of the laminate is 80% or more.
12. The method for manufacturing a battery according to claim 9, further comprising the following operations: The solid electrolyte material included in the positive electrode, the solid electrolyte layer, and the negative electrode is prepared by mixing raw material powders and firing them.
Citation Information
Patent Citations
Halide production method
WO2020136952A1